Pengaruh Metode STEAM Terhadap Perkembangan Fisik Motorik Anak Usia 4-5 Tahun di TKM NU 294 YA TAMAM - Masarrotur Rifadah; Ayunda Sayyidatul Ifadah; Fitri Ayu Fatmawati (Universitas Muhammadiyah Gresik, 2022)
This study aims to determine the results of the application of the STEAM method on the development of physical motor aspects in early childhood at the age of 4-5 years. Using the experimental method, the research design was posttest only control design by giving treatment to the experimental class and testing two classes, namely the control class and the experimental class. The results of this study indicate that the results of the control class using the demonstration method, the average value is 23.11, while for the experimental class using the STEAM method, the average value is 26.44. So that it can be concluded that there is an influence on students in aspects of physical motor development using the STEAM method obtained from the posttest data results. Keywords: Early Childhood, Motor Physics, Learning Methods, STEAM